Radiojornalismo de proximidade: o rompimento das fronteiras geográficas por meio do quadro Conexão Açaí-Cuxá (Parauapebas/PA-Imperatriz/MA) - SOUSA, Morgana Albuquerque (2023)
In search of understanding the proximity between Imperatriz (MA) and Parauapebas (PA), this research analyzed the Conexão Açaí-Cuxá segment, presented within the Alerta 96 program on Radio Arara Azul FM (96.9) in Parauapebas (PA), which is linked with the Rádio Alternativo program on Nativa FM (99.5) in Imperatriz (MA). The live link connects the municipalities through soundwaves for approximately ten minutes, presenting news from both cities from Monday to Friday around 10 a.m. This radio fusion has been ongoing for 13 years, implying its significance to the listening audience. From this perspective, the question arises: How does a short program connect two geographically distant cities and remain on the air for 13 years? To answer this question, qualitative and descriptive research was conducted in three stages: first, the listening of several segments that aired over seven weeks from 2021 to 2022 to observe the type of content being broadcasted. Second, a participant observation was carried out at both radio stations to understand the production routine and how information for the program is selected. In a third stage, semi-structured interviews (MARTINO, 2018) were conducted with the segment's presenters: Elson Brito, Arimatéia Júnior, and Demerval Moreno, as well as with the politician and owner of the stations, Raimundo Cabeludo, to understand how he perceived the need for information exchange between the municipalities. The main concept guiding the discussion is that of local journalism, which will be approached from the perspective of information proximity (PERUZZO, 2005; CAMPONEZ, 2011; AVRELLA, 2014; COMASSETTO, 2007; DORNELLES, 2010). Out of the total of 35 selected weeks for analysis, only 24 were broadcast. From these, a corpus of 233 pieces of information presented in the segment was obtained, divided between news and highlights. There were 156 news items identified, with 76% lacking identified sources. Throughout the analyzed editions, nine editorial topics were observed in the segment, with the police section being the most frequent, followed by general news, politics, and health. There is a considerable difference in the selection of local and regional information between the two stations. While Parauapebas presented 68 local pieces of information, Imperatriz only presented 34. In terms of regional information, Imperatriz had a slightly higher number at 67, while Parauapebas had 44. The segment is an example of proximity radio journalism; however, the primary form of proximity identified is between the cities connected by the program. The proximity of the content of the information presented in the segment is with the respective audiences of each station's cities. In other words, the proximity is between Arara Azul FM and the listening audience of Parauapebas and between Nativa FM and the listening audience of Imperatriz. Therefore, the target audience for Conexão Açaí-Cuxá is people who have an emotional connection to one of these cities and are interested in learning about their contexts, even if they are outside of them. Thus, the segment relies on this audience to remain on the air for thirteen years.